The Influence of Return On Assets, Debt To Equity Ratio, Price Earning Ratio on Stock Returns in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017 - 2019 Period - Verry, Verry; Afriani, Mila (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
A financial report is said to have information content if the publication of the financial report causes a market reaction. Market reaction refers to investors and other market players carrying out transactions (either buying or selling) shares in response to important decisions by issuers conveyed to the market. This market reaction is shown by changes in stock prices which are usually measured using stock returns as the change value. In this research, the research object of the researcher is manufacturing companies listed on the Indonesian Stock Exchange. Apart from that, Manufacturing Companies were also chosen because the majority of companies listed on the Indonesian Stock Exchange are Manufacturing Companies. Some of the differences between this research and previous research are that the financial ratios in previous research did not include market ratios. Meanwhile, this research takes into account market ratios as measured by the variables Return On Assets, Debt To Equity Ratio, PriceEarning Ratio and Stock Return variables as control variables. Most of the companies listed on the Indonesian Stock Exchange are manufacturing companies. Therefore, in this research, the research object of the researcher is manufacturing companies listed on the Indonesia Stock Exchange. The researcher is interested in conducting research by changing the independent variables used as a basis for examining the effect on the dependent variable.